Two distinct TP53 mutations in HNSCC primary tumor: Only one circulates in the blood. (April 2021) - Ganci, Federica; Allegretti, Matteo; Manciocco, Valentina; Fiorentino, Francesco; Sanguineti, Giuseppe; Giacomini, Patrizio; Pellini, Raul; Spinella, Francesca; Blandino, Giovanni
Highlights: NGS technology detects multiple mutations with very low allelic frequencies (<1%). Unpaired detection of mutations between tissues and matched plasma was found. Analysis of different tumoral tissue contributes to decipher intratumoral heterogeneity. NGS technology detects mutations in ctDNA revealing potential tumor cell spreading.